France : Report on the Observance of Standards and Codes - Data Module Update. (IMF Staff Country Reports; Country Report, 2005)
This paper presents an update to the Report on the Observance of Standards and Codes on Data Module for France. The paper discusses that France continues to observe the Special Data Dissemination Standard's specifications for the coverage, periodicity, and timeliness of all data categories, including the detailed template on international reserves and foreign currency liquidity, and for the dissemination of advance release calendars. The metadata and summary methodologies underlying the economic statistics are being regularly updated on the Dissemination Standards Bulletin Board.